Towards a digital native era in nutrition: introducing the m-format labeling - Bobe, Magdalena; Procopie, Roxana; Pamfilie, Rodica; Bumbac, Robert; Giușcă, Smaranda; Mihai, Mihaela; Jurconi, Alexandru (Journal of Business Economics and Management, 2024)
The advent of m-commerce has reinvented and simplified the shopping experience for the digital native generation. The following questions were the starting points for this research: is nutrition labeling important in purchase decisions? Could a new format for food nutrition labeling in m-commerce be the optimal way to inform the younger generation and enrich their shopping experience? This study continues the authors’ research on the food preferences of the younger generation by conducting a quantitative study on a sample of 364 students. The aim of the paper is to identify the factors that influence online food orders and the ways in which nutrition labeling can enhance consumers’ purchasing experiences and eating habits. The results show that nutrition facts play an important role in online purchases of new or unfamiliar foods. Control over one’s own diet and a higher income also make digital natives more interested in ordering food online. The use of a mobile format for nutrition labeling would be the necessary update for the food industry to turn nutrition data into added value, help consumers get a balanced diet and personalize nutritional needs, and for policymakers to adjust nutrition standards and policies toward healthier and more responsible consumption patterns.